Online Resources in MEMS Technology for Professional and Educational Development - Matthias W. Pleil; G.H. Massiha (Institute of Advanced Engineering and Science, 2014)
Over the last twenty years, the National Science Foundation (NSF) through its Advanced Technological Education (ATE) program has funded many ATE centers across the United State of America to advance the technician level work force in the Country. One of these centers is the Southwest Center for Microsystems Education (SCME) located at the University of New Mexico. The SCME offers educational materials and professional development at no cost. These materials and professional development opportunities include sponsored conferences, downloadable written materials for instructors and students, YouTube channels providing lectures, animations and videos, hands-on kits for the classroom, micro and nano films, webinars, online distance learning courses and mentoring opportunities for educators.DOI: http://dx.doi.org/10.11591/ijere.v3i1.5841